2015
DOI: 10.1186/s12868-015-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterisation of murine α4β1δ GABAA receptors expressed in Xenopus oocytes

Abstract: BackgroundGABAA receptor subunit composition has a profound effect on the receptor’s physiological and pharmacological properties. The receptor β subunit is widely recognised for its importance in receptor assembly, trafficking and post-translational modifications, but its influence on extrasynaptic GABAA receptor function is less well understood. Here, we examine the pharmacological properties of a potentially native extrasynaptic GABAA receptor that incorporates the β1 subunit, specifically composed of α4β1δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…However, the potencies of GABA and THIP at α 4 β 1 δ receptors determined in patch clamp electrophysiology were 5–8 times higher than that found using the FMP assay. Although we observed differences in the potency between the two assays, the FMP data are still within the range of what is reported in the literature, ranging from 0.89 to 2.02 μM and the difference between the potency of GABA and THIP is similar for both assays with THIP being 7 and 13 times less potent at α 4 β 1 δ receptors in the FMP and patch clamp assays, respectively. Additionally, no superagonism of THIP was found in the FMP assay at either of the studied ternary δ‐receptors, in contrast to the patch clamp studies on α 4 β 1 δ, where THIP was able to induce higher signals than GABA.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the potencies of GABA and THIP at α 4 β 1 δ receptors determined in patch clamp electrophysiology were 5–8 times higher than that found using the FMP assay. Although we observed differences in the potency between the two assays, the FMP data are still within the range of what is reported in the literature, ranging from 0.89 to 2.02 μM and the difference between the potency of GABA and THIP is similar for both assays with THIP being 7 and 13 times less potent at α 4 β 1 δ receptors in the FMP and patch clamp assays, respectively. Additionally, no superagonism of THIP was found in the FMP assay at either of the studied ternary δ‐receptors, in contrast to the patch clamp studies on α 4 β 1 δ, where THIP was able to induce higher signals than GABA.…”
Section: Discussionsupporting
confidence: 81%
“…In spite of the number of studies, the precise pharmacology of the δ‐containing GABA A receptors remains uncertain. Although not exclusively, studies performed on α 4 β 1/3 δ expressed in Xenopus laevis oocytes have reported biphasic GABA concentration–response curves with EC 50 values in the low nanomolar and low micromolar range, respectively, whereas monophasic GABA concentration–response curves with EC 50 values in the low micromolar range have typically been observed for receptors expressed in HEK cells . Explanations for these differences may relate to both differences in the biochemistry of the expression system, differences in transfection ratios and the species of the used subunits .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of cytosolic and extracellular putrescine has been determined to be 22 nmol/g and 12 nmol/g , respectively [ 339 ]. In contrast, copper may decrease tonic inhibition via acting on delta subunit-containing extrasynaptic GABA A receptors [ 235 , 237 , 246 ], thus adding a new layer to disinhibitory mechanisms in copper-rich brain areas.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Moreover there are some possible effect of species differences in alcohol and alcohol antagonist responses (Wallner, et al, 2014). For example, a recent study suggests that there are some significant differences in the pharmacology of murine and human α4β1δ receptors (Villumsen et al, 2015). Therefore, it is clear that methodological issues should be carefully considered for studies with -GABAARs in general and for the effects of alcohol on these receptors in particular.…”
Section: Alcohol and Extra-synaptic Gabaarsmentioning
confidence: 99%